Application of Collaborative Teamwork Learning Model and Guided Note Taking Model and Their Influence on Students' Ability to Understand Mathematical Concepts - Arif Muchyidin; Nurma Izzati; Khannatus Sa’diyah (MASI Mandiri Edukasi, 2022)
The purpose of this study was to determine the ability to understand students' mathematical concepts and the responses of students who applied the collaborative teamwork learning model and guided note-taking model, as well as to find out the differences in understanding the mathematical concepts of students who applied the collaborative teamwork learning model and the guided note taking model. This study uses a quantitative approach with experimental methods and a quasi-experimental research design in the form of a posttest-only design. The population of this study were students of class X MAN 1 Cirebon, Cirebon Regency, then selected samples of class X IIS 3 as experimental class II with guided note-taking model and X IIS 4 as experimental class I with collaborative teamwork learning model. Sampling is done by cluster random sampling technique. Through the prerequisite test, namely the normality and homogeneity test, the research data obtained were normally distributed and had homogeneous variance. After conducting the prerequisite test, the researcher tested the hypothesis using the Independent Sample T-Test with the asymp value. Sig (2-tailed) of 0.000. This value is smaller than 0.05, so Ha is accepted. In other words, there are differences in the understanding of mathematical concepts between classes that apply the collaborative teamwork learning model with guided note-taking models on the subject of the sine and cosine rules in class X IIS MAN Cirebon I Cirebon Regency. The average value of the class that applies the collaborative teamwork learning model is 72.38, with 11 students achieving the KKM (Minimum Completeness Criteria), and the guided note-taking model of 78.52, with 29 students completing the KKM (Minimum Completeness Criteria). Both models received a good response from students, with a response of 82% for the collaborative teamwork learning model and 76% for the guided note-taking model.